Of soya beans & sweet potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Learn how to grow sweet potatoes P B Ngeze, Acacia Stantex Publishers/CTA/Friends-of-the-Book Foundation, 2000. 45 pp. ISBN 9966 917 11 x CTA number 997. 5 credit points